Evaluasi Nilai Kalor Batubara terhadap Efisiensi Boiler PLTU Suralaya - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Wahyu Haristiyanto (JTM : JURNAL TEKNIK MESIN, 2026)
Coal calorific value affects the heat input, combustion quality, heat losses, and fuel consumption of steam power plant boilers. This paper evaluates the effect of coal calorific value on boiler efficiency at Units 1, 3, and 4 of PLTU Suralaya. The study uses performance test data at a comparable load of 400 MW with coal calorific values of 4238, 4472, 4656, and 5051 kcal/kg. Boiler efficiency is calculated using the direct method and the indirect heat loss method based on ASME PTC 4.1. The indirect method shows that boiler efficiency increases from 83.269% at 4238 kcal/kg to 86.625% at 5051 kcal/kg. Total heat loss decreases from 16.731% to 13.375%, while specific fuel consumption decreases from 0.613 to 0.553 kg/kWh. The results indicate that higher coal calorific value improves boiler efficiency and reduces coal consumption, mainly because lower moisture and higher fixed carbon reduce heat losses in flue gas and moisture evaporation